An electric equipment unpowered high-efficiency heat dissipation shell and a preparation method thereof

CN122992516APending Publication Date: 2026-10-27SICHUAN TAILI ELECTRICAL WHOLE-SET CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611477372.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明的目的在于:提供了一种电气设备无动力高效散热外壳及其制备方法,解决了现有电气设备金属外壳基体与外壳表面功能涂层之间无法形成有效的导热通道,容易导致涂层结构破坏及整体散热效率的问题

Benefits of technology

[0028]1.本发明一种电气设备无动力高效散热外壳中内层涂层以腰果酚-糠胺型苯并噁嗪/丙烯酸酯IPN树脂为基体,以苯硼酸/多巴胺复合修饰的巯基化氮化硼/乙烯基化碳化硅复合物为核心导热填料,通过“巯基-烯”点击化学形成BN—SiC共价键连接,通过苯硼酸形成动态硼酸酯键,构建内层导热网络;外层涂层以环碳酸酯化聚硅氧烷和含氟丙烯酸酯三元共聚物为基体,以胺基改性的碳纤维掺杂ZIF-8衍生物负载石墨烯/氮化铝复合物为核心导热填料,构建外层导热网络;内层导热网络、基体、外层导热网络形成了从内至外的导热通道,具有好的散热效果,在电气设备不出现内部异常高温等情况时,能够维持日常的正常无动力散热;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992516A_ABST
    Figure CN122992516A_ABST
Patent Text Reader

Abstract

The application discloses an electric equipment non-powered efficient heat dissipation shell and a preparation method thereof, and belongs to the technical field of electric equipment structure processing, and comprises a base body, an inner coating and an outer coating; the base body is prepared from a silicon carbide particle reinforced aluminum matrix composite material; the inner coating comprises a cardanol-furfuryl amine type benzoxazine / acrylate IPN resin precursor, a phenylboronic acid / dopamine composite modified sulfhydrylated boron nitride / vinylated silicon carbide compound, an aminated aluminum oxide, a cardanol glycidyl ether, a propylene glycol methyl ether acetate, an organic tin catalyst and a benzoyl peroxide initiator; and the outer coating comprises a cyclic carbonate polysiloxane, a glycidyl methacrylate / perfluorohexylethyl methacrylate / itaconic acid terpolymer, a polyamine curing agent, an amine group modified carbon fiber doped ZIF-8 derivative loaded graphene derivative / aluminum nitride compound, a DBU / TU two-component catalyst and a mixed solvent. The application improves the heat dissipation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of power equipment structure processing technology, and relates to a non-powered high-efficiency heat dissipation shell for electrical equipment and its preparation method; it is applicable not only to outdoor power distribution devices, but also to indoor power distribution devices. Background Technology

[0002] The main casings of existing electrical equipment such as JP integrated distribution boxes, integrated primary and secondary ring network boxes, box-type substations and pole-mounted circuit breakers are made of metal. Metal casings have good thermal conductivity and provide a certain degree of non-powered heat dissipation for the internal components of electrical equipment.

[0003] However, metal casings have poor corrosion resistance and generally require a functional coating to be applied to the surface. The main components of the functional coating are high molecular polymers such as resins, which have low thermal conductivity and poor thermal performance. The coating cannot establish an effective heat conduction channel with the substrate. This causes a large amount of heat to accumulate at the interface between the coating and the substrate, forming a "stale heat" effect, which seriously reduces the overall heat dissipation efficiency. At the same time, the "stale heat" effect makes the coating easy to peel off and crack. Summary of the Invention

[0004] The purpose of this invention is to provide a non-powered, high-efficiency heat dissipation housing for electrical equipment and its preparation method, which solves the problem that existing electrical equipment cannot form an effective heat conduction channel between the metal housing substrate and the functional coating on the housing surface, which easily leads to damage to the coating structure and overall heat dissipation efficiency.

[0005] The technical solution adopted in this invention is as follows:

[0006] A non-powered, high-efficiency heat dissipation housing for electrical equipment includes a substrate, an inner coating, and an outer coating. The inner coating is attached to the inner surface of the substrate, and the outer coating is attached to the outer surface of the substrate. The thickness of the substrate is 4-6 mm, the thickness of the inner coating is 60-70 μm, and the thickness of the outer coating is 80-100 μm.

[0007] The matrix was prepared from silicon carbide particle-reinforced aluminum matrix composite material;

[0008] The inner coating comprises the following components in parts by weight: 40-45 parts of cashew nut shell powder-furfurylamine type benzoxazine / acrylate IPN resin precursor, 20-25 parts of phenylboronic acid / dopamine composite modified thiolated boron nitride / vinylened silicon carbide complex, 10-13 parts of aminated alumina, 5-10 parts of cashew nut shell powder glycidyl ether, 30-40 parts of propylene glycol methyl ether acetate, 0.5-0.6 parts of organotin catalyst, and 0.3-0.5 parts of benzoyl peroxide initiator;

[0009] The outer coating comprises the following components in parts by weight: 45-50 parts of cyclic carbonated polysiloxane, 15-20 parts of glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer, 5-8 parts of polyamine curing agent, 25-28 parts of amine-modified carbon fiber doped ZIF-8 derivative supported graphene derivative / aluminum nitride composite, 0.5-1 parts of DBU / TU bicomponent catalyst, and 30-40 parts of mixed solvent; the mixed solvent is propylene glycol methyl ether acetate and butyl acetate in a volume ratio of 1:1.

[0010] Furthermore, the carbon fiber doped with ZIF-8 derivative is a calcined product of ZIF-8@PVP composite and lignin-based carbon fiber at 610°C.

[0011] Furthermore, the cashew phenol-furfurylamine type benzoxazine / acrylate IPN resin precursor is obtained by uniformly mixing cashew phenol-furfurylamine type benzoxazine monomer, acrylate prepolymer and crosslinking agent dimethacrylate in a mass ratio of 4:5:1.

[0012] Further, the phenylboronic acid / dopamine composite modified mercaptoboron nitride / vinyl silicon carbide composite is prepared by the following method: mercaptoboron nitride and vinyl silicon carbide are dispersed in N,N-dimethylformamide at a mass ratio of 2:1, and 3% of the total mass of mercaptoboron nitride and vinyl silicon carbide photoinitiator 2,2-dimethoxy-2-phenylacetophenone is added. The reaction is carried out under ultraviolet light irradiation for 2-4 hours. Subsequently, the phenylboronic acid / dopamine composite is added, with the amount of phenylboronic acid / dopamine composite being 6% of the total mass of mercaptoboron nitride and vinyl silicon carbide. The reaction is continued with stirring for 2-4 hours, followed by centrifugation, washing, and drying to obtain the phenylboronic acid / dopamine composite modified mercaptoboron nitride / vinyl silicon carbide composite.

[0013] Further, the aminated alumina is prepared by dispersing 30 nm α-alumina nanoparticles in toluene, adding 5% of γ-aminopropyltriethoxysilane by mass of the α-alumina nanoparticles, and refluxing at 110 °C for 6-8 hours; after the reaction is completed, centrifuging is performed, followed by washing and vacuum drying at 60 °C for 12 hours to obtain aminated alumina.

[0014] Further, the glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer was prepared by the following method: glycidyl methacrylate, perfluorohexyl ethyl methacrylate and itaconic acid were mixed and dissolved in butyl acetate at a molar ratio of 3:2:1, and 1% of the total mass of the monomers was added as an azobisisobutyronitrile initiator. The mixture was heated to 70°C under nitrogen protection, stirred and reacted for 12 hours, precipitated in diethyl ether, and dried under vacuum to obtain the terpolymer.

[0015] Furthermore, the amino-modified carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was prepared by the following method: zinc nitrate hexahydrate and 2-methylimidazole were dissolved in methanol at a mass ratio of 1:2.5. The 2-methylimidazole solution was slowly added to the zinc nitrate solution under stirring. Then, polyvinylpyrrolidone (PVP) at 20% of the mass of zinc nitrate was added, and the mixture was stirred at room temperature for 2-4 hours. After the reaction was completed, the mixture was centrifuged, washed, and dried at 60°C for 12 hours to obtain the ZIF-8@PVP composite.

[0016] Lignocellulose-based carbon fibers with a diameter of 100 nm to 200 nm and an aspect ratio of 150, prepared by electrospinning of alkali lignin with a lignin purity of 70%, were dispersed in anhydrous ethanol and ultrasonically treated for 30 minutes to obtain a suspension. ZIF-8@PVP composite was added to the suspension, with a mass ratio of ZIF-8@PVP to lignin-based carbon fibers of 3.5:1. After stirring and mixing for 2 hours, the mixture was centrifuged and dried at 60 °C to obtain the ZIF-8@PVP / lignin-based carbon fiber composite precursor.

[0017] The ZIF-8@PVP / lignin-based carbon fiber composite precursor was placed in a tube furnace and heated to 610°C at a heating rate of 3°C / min under argon protection, and held for calcination for 2-4 hours; it was then naturally cooled to room temperature to obtain carbon fiber-doped ZIF-8 derivatives.

[0018] Graphene oxide, nano-aluminum nitride, and carbon fiber-doped ZIF-8 derivative were dispersed in N,N-dimethylformamide at a mass ratio of 1:2:10. The mixture was ultrasonically dispersed for 1-2 hours, transferred to a hydrothermal reactor, and reacted at 150°C for 18 hours. After cooling, washing, and drying, a carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was obtained.

[0019] Carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was dispersed in anhydrous toluene, and 10% (3-aminopropyl)triethoxysilane (by mass) of the carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was added. The mixture was heated to 80℃~110℃ and refluxed for 10h~12h. After centrifugation, washing and drying, amine-modified carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was obtained.

[0020] Furthermore, the organotin catalyst is dibutyltin dilaurate.

[0021] Furthermore, the polyamine curing agent is triethylenetetramine; the mass ratio of DBU to TU in the DBU / TU bicomponent catalyst is 2:1.

[0022] The method for preparing a non-powered, high-efficiency heat dissipation casing for electrical equipment includes the following steps:

[0023] S1. Preparation of the substrate: Silicon carbide particles with a particle size of 10~50μm are placed in an air atmosphere and pre-oxidized at 500℃ for 3 hours to obtain pre-oxidized silicon carbide particles; the pre-oxidized silicon carbide particles are mixed with 6061 aluminum alloy powder at a volume ratio of 45:55, and then magnesium powder accounting for 2% of the total mass of the mixed powder is added. The mixture is ball-milled for 1.5 hours, dried and sieved to obtain a mixed powder; the obtained mixed powder is cold-pressed under a pressure of 50MPa to obtain a cold-pressed blank; the cold-pressed blank is placed in a hot press furnace, and under inert gas protection, the temperature is first raised to 580℃, held at 35MPa for 15 minutes, then raised to 620℃, held at 30MPa for 3 hours, and cooled to room temperature with the furnace to obtain a substrate with a thickness of 4~6mm; the inner and outer surfaces of the substrate are roughened by sandblasting, and then ultrasonically cleaned with acetone and ethanol for 15 minutes in sequence, and dried at 60℃ to obtain a surface-treated substrate for later use;

[0024] S2. Inner Coating: 40-45 parts of cashew phenol-furfurylamine type benzoxazine / acrylate IPN resin precursor, 20-25 parts of phenylboronic acid / dopamine composite modified mercaptolated boron nitride / vinylened silicon carbide composite, 10-13 parts of aminated alumina, 5-10 parts of cashew phenol glycidyl ether, 30-40 parts of propylene glycol methyl ether acetate, 0.5-0.6 parts of organotin catalyst, and 0.3-0.5 parts of benzoyl peroxide initiator are sequentially added to a dispersion vessel and dispersed at a high speed of 800-1500 rpm for 30-60 minutes. Then, the mixture is transferred to a sand mill and ground to a fineness ≤20 μm to obtain the inner coating. The inner coating is uniformly coated onto the inner surface of the substrate by air spraying. After leveling at room temperature for 10-20 minutes, the coating is placed in an oven for stepwise temperature curing to form an inner coating with a thickness of 60-70 μm.

[0025] S3. Outer Coating: 45-50 parts of cyclic carbonated polysiloxane, 15-20 parts of glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer, and 30-40 parts of mixed solvent are mixed evenly, and then 25-28 parts of amine-modified carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite are added. The mixture is dispersed at a high speed of 1000-2000 r / min for 30-60 min and ground to a fineness ≤20 μm. Before coating, 5-8 parts of polyamine curing agent and 0.5-1 parts of DBU / TU bicomponent catalyst are added, stirred evenly, and cured for 10-20 min to obtain the outer coating. The outer coating is evenly coated onto the outer surface of the substrate by air spraying. After leveling at room temperature for 15-30 min, it is cured at 100℃ for 4 h to form an outer coating with a thickness of 80 μm-100 μm.

[0026] S4. After coating the inner and outer surfaces of the substrate, allow it to cool naturally to room temperature to obtain a high-efficiency heat dissipation shell material for electrical equipment without power.

[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] 1. The present invention discloses an electrical equipment non-powered high-efficiency heat dissipation shell. The inner coating uses cashew phenol-furfurylamine type benzoxazine / acrylate IPN resin as the matrix and a phenylboronic acid / dopamine composite modified with mercapto-boron nitride / vinyl silicon carbide as the core thermally conductive filler. The inner thermally conductive network is constructed by forming BN-SiC covalent bonds through "mercapto-olefin" click chemistry and dynamic borate ester bonds through phenylboronic acid. The outer coating uses cyclic carbonated polysiloxane and fluorinated acrylate terpolymer as the matrix and an amino-modified carbon fiber doped with ZIF-8 derivative loaded with graphene / aluminum nitride composite as the core thermally conductive filler. The inner thermally conductive network, the matrix, and the outer thermally conductive network form a heat conduction channel from the inside to the outside, which has a good heat dissipation effect and can maintain normal non-powered heat dissipation when the electrical equipment does not experience abnormal internal high temperature.

[0029] 2. In addition to providing basic corrosion protection, the inner and outer coatings of this invention establish an effective heat conduction channel between the coating and the substrate through the core thermally conductive filler, avoiding a "suffocating" effect between the coating and the substrate, which helps to improve the overall thermal conductivity of the shell and thus improve the heat dissipation effect. Attached Figure Description

[0030] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort, wherein:

[0031] Figure 1 This is a physical image of the high-efficiency heat dissipation shell material for electrical equipment prepared in Example 1;

[0032] Figure 2 This is a photograph of the outer shell material prepared in Example 1 being used in a JP cabinet.

[0033] Figure 3 This is a comparison image of the outer surface of the sample from Example 1 after 1000 thermal cycles with the outer surface micrographs of the samples from Comparative Examples 1-4. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, and not all embodiments. The components of the embodiments of the invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0035] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.

[0036] It should be noted that relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0037] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0038] This invention provides a non-powered, high-efficiency heat dissipation housing for electrical equipment, comprising a substrate, an inner coating layer, and an outer coating layer. The inner coating layer is attached to the inner surface of the substrate, and the outer coating layer is attached to the outer surface of the substrate. The thickness of the substrate is 4-6 mm, the thickness of the inner coating layer is 60-70 μm, and the thickness of the outer coating layer is 80-100 μm. The substrate is prepared from a silicon carbide particle-reinforced aluminum matrix composite material.

[0039] In the following embodiments, the inner coating comprises the following components in parts by weight: 40-45 parts of cashew nut shell powder-furfurylamine type benzoxazine / acrylate IPN resin precursor, 20-25 parts of phenylboronic acid / dopamine composite modified thiolated boron nitride / vinylened silicon carbide composite, 10-13 parts of aminated alumina, 5-10 parts of cashew nut shell powder glycidyl ether, 30-40 parts of propylene glycol methyl ether acetate, 0.5-0.6 parts of organotin catalyst, and 0.3-0.5 parts of benzoyl peroxide initiator;

[0040] In the following embodiments, the outer coating comprises the following components in parts by weight: 45-50 parts of cyclic carbonated polysiloxane, 15-20 parts of glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer, 5-8 parts of polyamine curing agent, 25-28 parts of amine-modified carbon fiber doped ZIF-8 derivative supported graphene derivative / aluminum nitride composite, 0.5-1 parts of DBU / TU bicomponent catalyst, and 30-40 parts of mixed solvent; the mixed solvent is propylene glycol methyl ether acetate and butyl acetate in a volume ratio of 1:1.

[0041] In the following examples, the cashew nut phenol-furfurylamine type benzoxazine / acrylate IPN resin precursor is prepared by uniformly mixing cashew nut phenol-furfurylamine type benzoxazine monomer, acrylate prepolymer, and crosslinking agent ethylene glycol dimethacrylate in a mass ratio of 4:5:1; the preparation method is as follows:

[0042] Cashew nut phenol, furfurylamine and paraformaldehyde were added to a reactor in a molar ratio of 1:1:2. The mixture was refluxed at 120°C for 7 hours using toluene as a solvent. The cashew nut phenol-furfurylamine type benzoxazine monomer was obtained by vacuum distillation.

[0043] Methyl methacrylate, butyl acrylate, and hydroxyethyl methacrylate were mixed in a mass ratio of 50:30:15 to obtain a mixed monomer. Azobisisobutyronitrile (AIBN) was added as an initiator at 0.5% of the total mass of the mixed monomers. The mixture was then subjected to solution prepolymerization at 80°C for 2 hours under nitrogen protection to obtain an acrylate prepolymer.

[0044] Cashew phenol-furfurylamine type benzoxazine monomer, acrylate prepolymer and crosslinking agent ethylene glycol dimethacrylate were mixed evenly at a mass ratio of 4:5:1 to obtain cashew phenol-furfurylamine type benzoxazine / acrylate IPN resin precursor.

[0045] In the following examples, the phenylboronic acid / dopamine composite modified with thiolized boron nitride / vinylened silicon carbide was prepared by the following method:

[0046] (a) Preparation of thiolized boron nitride: Hexagonal boron nitride nanosheets were dispersed in a 9:1 volume ratio of ethanol / water mixed solvent and ultrasonically dispersed for 2 h. 13% (3-mercaptopropyl)trimethoxysilane by mass of hexagonal boron nitride was added. The pH was adjusted to 4.5 with acetic acid, the temperature was raised to 70 °C, and the reaction was stirred for 18 h. After centrifugation, washing and drying, thiolized boron nitride was obtained.

[0047] (b) Preparation of vinylized silicon carbide: Silicon carbide nanowires were dispersed in anhydrous toluene, and 10% by weight of vinyltrimethoxysilane was added. The mixture was ultrasonically dispersed for 45 min, heated to 100 °C, refluxed for 18 h, centrifuged, washed and dried to obtain vinylized silicon carbide.

[0048] (c) Preparation of phenylboronic acid / dopamine complex: 4-carboxyphenylboronic acid and dopamine were dissolved in Tris-HCl buffer at pH 8.5 at a molar ratio of 1:1.5 and stirred at room temperature for 3 h to obtain phenylboronic acid / dopamine complex.

[0049] (d) Composite assembly: Thiolated boron nitride and vinylized silicon carbide were dispersed in N,N-dimethylformamide at a mass ratio of 2:1. 3% of the total mass of thiolated boron nitride and vinylized silicon carbide was added as a photoinitiator, 2,2-dimethoxy-2-phenylacetophenone, and the mixture was reacted under ultraviolet light for 4 h. Subsequently, a phenylboronic acid / dopamine composite was added at a mass of 6% of the total mass of thiolated boron nitride and vinylized silicon carbide. The mixture was stirred and reacted for another 4 h. After centrifugation, washing, and drying, the phenylboronic acid / dopamine composite modified thiolated boron nitride / vinylized silicon carbide composite was obtained.

[0050] In the following examples, the aminated alumina was prepared by dispersing 30 nm α-alumina nanoparticles in toluene, adding 5% γ-aminopropyltriethoxysilane by mass of the α-alumina nanoparticles, and refluxing at 110 °C for 7 hours. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 60 °C for 12 hours to obtain aminated alumina.

[0051] In the following examples, the glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer was prepared by the following method: glycidyl methacrylate, perfluorohexyl ethyl methacrylate and itaconic acid were mixed and dissolved in butyl acetate at a molar ratio of 3:2:1, and 1% of azobisisobutyronitrile initiator by the total mass of monomers was added. The mixture was heated to 70°C under nitrogen protection, stirred and reacted for 12 hours, precipitated in diethyl ether, and dried under vacuum to obtain the terpolymer.

[0052] In the following examples, the carbon fiber doped ZIF-8 derivative is a calcined product of ZIF-8@PVP composite and lignin-based carbon fiber at 610°C; the amine-modified carbon fiber doped ZIF-8 derivative loaded with graphene derivative / aluminum nitride composite is prepared by the following method: zinc nitrate hexahydrate and 2-methylimidazole are dissolved in methanol at a mass ratio of 1:2.5, and the 2-methylimidazole solution is slowly added to the zinc nitrate solution under stirring; then polyvinylpyrrolidone (PVP, K30) accounting for 20% of the mass of zinc nitrate is added, and the reaction is stirred at room temperature for 4 hours; after the reaction is completed, the mixture is centrifuged, washed, and dried at 60°C for 12 hours to obtain the ZIF-8@PVP composite.

[0053] Lignocellulose-based carbon fibers with a diameter of 100 nm to 200 nm and an aspect ratio of 150, prepared by electrospinning of alkali lignin with a lignin purity of 70%, were dispersed in anhydrous ethanol and ultrasonically treated for 30 minutes to obtain a suspension. ZIF-8@PVP composite was added to the suspension, with a mass ratio of ZIF-8@PVP to lignin-based carbon fibers of 3.5:1. After stirring and mixing for 2 hours, the mixture was centrifuged and dried at 60 °C to obtain the ZIF-8@PVP / lignin-based carbon fiber composite precursor.

[0054] The ZIF-8@PVP / lignin-based carbon fiber composite precursor was placed in a tube furnace and heated to 610°C at a heating rate of 3°C / min under argon protection, and held for calcination for 3 hours; it was then naturally cooled to room temperature to obtain carbon fiber-doped ZIF-8 derivatives.

[0055] Graphene oxide, nano-aluminum nitride, and carbon fiber-doped ZIF-8 derivative were dispersed in N,N-dimethylformamide at a mass ratio of 1:2:10. The mixture was ultrasonically dispersed for 2 hours, transferred to a hydrothermal reactor, and reacted at 150°C for 18 hours. After cooling, washing, and drying, a carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was obtained.

[0056] Carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was dispersed in anhydrous toluene, and 10% (3-aminopropyl)triethoxysilane (by mass) of the carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was added. The mixture was heated to 100℃ and refluxed for 12 h. After centrifugation, washing and drying, amine-modified carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was obtained.

[0057] In the following examples, the organotin catalyst is dibutyltin dilaurate.

[0058] In the following examples, the polyamine curing agent is triethylenetetramine; the mass ratio of DBU to TU in the DBU / TU bicomponent catalyst is 2:1.

[0059] Based on the above, the specific implementation of the present invention is as follows:

[0060] Example 1

[0061] A preferred embodiment of the present invention provides a high-efficiency heat dissipation housing for electrical equipment without power, which is prepared by the following method:

[0062] S1. Preparation of the matrix: Silicon carbide particles with a particle size of 10~50μm are placed in an air atmosphere and pre-oxidized at 500℃ for 3 hours to obtain pre-oxidized silicon carbide particles; the pre-oxidized silicon carbide particles are mixed with 6061 aluminum alloy powder at a volume ratio of 45:55, and then magnesium powder accounting for 2% of the total mass of the mixed powder is added. The mixture is ball-milled for 1.5 hours, dried, and sieved to obtain a mixed powder; the obtained mixed powder is cold-pressed under a pressure of 50MPa to obtain a cold-pressed blank; the cold-pressed blank is then... The pressed blank is placed in a hot press furnace and heated to 580°C under inert gas protection. It is then held at 35 MPa for 15 minutes, heated to 620°C, and held at 30 MPa for 3 hours. After cooling to room temperature in the furnace, a substrate with a thickness of 6 mm is obtained. The inner and outer surfaces of the substrate are roughened by sandblasting (alumina sand, particle size 24-60 mesh). Then, it is ultrasonically cleaned with acetone and ethanol for 15 minutes in sequence and dried at 60°C to obtain a surface-treated substrate for later use.

[0063] S2, Inner Coating: 43 parts of cashew nut shell powder-furfurylamine type benzoxazine / acrylate IPN resin precursor, 23 parts of phenylboronic acid / dopamine composite modified thiolated boron nitride / vinylened silicon carbide complex, 12 parts of aminated alumina, 8 parts of cashew nut shell powder glycidyl ether, 35 parts of propylene glycol methyl ether acetate, 0.6 parts of organotin catalyst, and 0.4 parts of benzoyl peroxide initiator were sequentially added to a dispersion vessel and dispersed at a high speed of 1200 r / min for 45 min, then transferred to… The inner coating is obtained by grinding the material in a sand mill to a fineness of ≤20μm. The inner coating is then uniformly applied to the inner surface of the substrate by air spraying. After leveling at room temperature for 15 minutes, the material is placed in an oven for step-by-step curing. The step-by-step curing method is as follows: the temperature is raised to 80℃ and held for 1 hour, then raised to 120℃ and held for 1 hour, and finally raised to 200℃ and held for 2 hours. The heating rate of each stage is 2℃ / min. The material is then cooled to room temperature to form an inner coating with a thickness of 70μm.

[0064] S3. Outer Coating: 48 parts of cyclic carbonated polysiloxane, 17 parts of glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer, and 35 parts of mixed solvent were mixed evenly, and then 26 parts of amine-modified carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite were added. The mixture was dispersed at 1500 r / min for 45 min and ground to a fineness ≤20 μm. Before coating, 6.5 parts of polyamine curing agent and 0.8 parts of DBU / TU bicomponent catalyst were added, stirred evenly, and cured for 20 min to obtain the outer coating. The outer coating was evenly coated onto the outer surface of the substrate by air spraying. After leveling at room temperature for 20 min, it was cured at 100℃ for 4 h to form an outer coating with a thickness of 100 μm.

[0065] S4. After coating the inner and outer surfaces of the substrate, allow it to cool naturally to room temperature to obtain a high-efficiency heat dissipation shell material for electrical equipment without power supply. See the image below. Figure 1 As shown; the application of the outer shell material in the JP cabinet is as follows. Figure 2 As shown.

[0066] Example 2

[0067] This embodiment differs from Example 1 only in that the formulations of the inner and outer coatings are different. The inner coating in this embodiment comprises the following components in parts by weight: 40 parts cashew nut shell powder-furfurylamine type benzoxazine / acrylate IPN resin precursor, 20 parts phenylboronic acid / dopamine composite modified mercaptolated boron nitride / vinylened silicon carbide complex, 10 parts aminated alumina, 5 parts cashew nut shell powder glycidyl ether, 30 parts propylene glycol methyl ether acetate, 0.5 parts organotin catalyst, and 0.3 parts benzoyl peroxide initiator;

[0068] In this embodiment, the outer coating comprises the following components in parts by weight: 45 parts cyclocarbonate-modified polysiloxane, 15 parts glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer, 5 parts polyamine curing agent, 25 parts amine-modified carbon fiber-doped ZIF-8 derivative supported graphene derivative / aluminum nitride composite, 0.5 parts DBU / TU bicomponent catalyst, and 30 parts mixed solvent; the mixed solvent is propylene glycol methyl ether acetate and butyl acetate in a volume ratio of 1:1. The rest is consistent with Example 1.

[0069] Example 3

[0070] This embodiment differs from Example 1 only in that the formulations of the inner and outer coatings are different. The inner coating in this embodiment comprises the following components in parts by weight: 45 parts cashew nut shell powder-furfurylamine type benzoxazine / acrylate IPN resin precursor, 25 parts phenylboronic acid / dopamine composite modified mercaptolated boron nitride / vinylened silicon carbide composite, 13 parts aminated alumina, 10 parts cashew nut shell powder glycidyl ether, 40 parts propylene glycol methyl ether acetate, 0.6 parts organotin catalyst, and 0.5 parts benzoyl peroxide initiator.

[0071] In this embodiment, the outer coating comprises the following components in parts by weight: 50 parts cyclocarbonate-modified polysiloxane, 20 parts glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer, 8 parts polyamine curing agent, 28 parts amine-modified carbon fiber-doped ZIF-8 derivative supported graphene derivative / aluminum nitride composite, 1 part DBU / TU bicomponent catalyst, and 40 parts mixed solvent; the mixed solvent is propylene glycol methyl ether acetate and butyl acetate in a volume ratio of 1:1. The rest is consistent with Example 1.

[0072] Comparative Example 1

[0073] This comparative example provides a heat dissipation housing for electrical equipment, comprising a 6mm thick 6061 aluminum alloy substrate, an outer coating of a 100μm thick polyurethane coating on the 6061 aluminum alloy substrate, and an inner coating of a 70μm thick polyurethane coating. It is prepared by the following method: 60 parts by weight of hydroxyl acrylic resin, 10 parts by weight of rutile titanium dioxide, 0.5 parts by weight of leveling agent BYK-333, 0.5 parts by weight of defoamer BYK-066N, and 15 parts by weight of butyl acetate are sequentially added to a dispersion vessel at a concentration of 12... Disperse at 00 r / min for 30 minutes, then transfer to a sand mill and grind to a fineness of ≤25 μm to obtain the polyurethane coating main agent; before coating, add 25 parts by weight of isocyanate curing agent (HDI trimer, NCO content 21.5%), stir evenly, and cure for 15 minutes; use air spraying to evenly coat the polyurethane coating on the inner and outer surfaces of the 6061 aluminum alloy substrate, level at room temperature for 15 minutes, and then cure at 80℃ for 4 hours to form polyurethane coatings with thicknesses of 70 μm (inner surface) and 100 μm (outer surface), respectively.

[0074] Comparative Example 2

[0075] This comparative example provides a heat dissipation housing for electrical equipment, comprising a 6mm thick 6061 aluminum alloy substrate, an outer coating of a 100μm thick epoxy coating on the 6061 aluminum alloy substrate, and an inner coating of a 70μm thick epoxy coating; prepared by the following method: 55 parts by weight of bisphenol A type epoxy resin (E-44 epoxy resin), 8 parts by weight of reactive diluent butyl glycidyl ether, 10 parts by weight of alumina filler (particle size 5~10μm), 5 parts by weight of silica powder, 0.5 parts by weight of defoamer BYK-066N, 12 Xylene and n-butanol were added sequentially to a dispersion vessel and dispersed at 1200 r / min for 30 minutes. The mixture was then transferred to a sand mill and ground to a fineness of ≤25 μm to obtain the epoxy coating main agent. Before coating, 20 parts by weight of T-31 curing agent were added, stirred evenly, and cured for 10 minutes. The epoxy coating was uniformly coated on the inner and outer surfaces of the 6061 aluminum alloy substrate by air spraying. After leveling at room temperature for 15 minutes, it was cured at 120℃ for 3 hours to form epoxy coatings with thicknesses of 70 μm (inner surface) and 100 μm (outer surface), respectively.

[0076] Comparative Example 3

[0077] The electrical equipment heat dissipation shell provided in this comparative example uses the substrate of Example 1. Both the outer coating and the inner coating use the polyurethane coating of Comparative Example 1, and the thickness is the same as in Example 1. The preparation method is the same as in Comparative Example 1.

[0078] Comparative Example 4

[0079] The electrical equipment heat dissipation shell provided in this comparative example uses the substrate of Example 1, and the outer coating and inner coating both use the epoxy coating of Comparative Example 2, with the thickness referring to Example 1; the preparation method refers to Comparative Example 2.

[0080] Comparative Example 5

[0081] Based on Example 1, the difference from Example 1 is that the inner coating of this comparative example does not contain the phenylboronic acid / dopamine composite modified mercaptolated boron nitride / vinylened silicon carbide composite; all other aspects are the same.

[0082] Comparative Example 6

[0083] Based on Example 1, the difference from Example 1 is that the coating layer of this comparative example does not contain amine-modified carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite; all other aspects are the same.

[0084] Comparative Example 7

[0085] Based on Example 1, the difference from Example 1 is that the inner coating of this comparative example does not contain the phenylboronic acid / dopamine composite modified mercaptolated boron nitride / vinylened silicon carbide composite; the outer coating does not contain the amine-modified carbon fiber doped ZIF-8 derivative loaded graphene derivative / aluminum nitride composite; all other aspects are the same.

[0086] Comparative Example 8

[0087] Based on Example 1, the difference from Example 1 is that this comparative exception layer coating does not contain the glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer. All other aspects are the same.

[0088] Test case

[0089] (1) The thermal resistance of the heat dissipation shells of electrical equipment prepared in Examples 1-3 and Comparative Examples 1-8 was tested. Referring to the standard ASTM D5470, the sample was clamped between the hot end and the cold end at a constant temperature to establish a steady-state unidirectional heat flow. The total thermal resistance was calculated by measuring the temperature difference and the heat flow density on both sides of the sample. For the coating / substrate composite structure, the thermal resistance contribution of the coating / substrate interface can be calculated by comparing the total thermal resistance of the bare substrate and the coated substrate. 25.4 mm diameter circular samples were cut from the shell materials prepared in each example and comparative example. The inner coating (70 μm thick) and the outer coating (100 μm thick) were intact. At the same time, bare substrate samples (without coating) of the same batch (corresponding to each example and comparative example) were prepared as references. Three parallel samples were prepared for each group of samples. The loading pressure was set to 0.5 MPa, the hot end temperature was 80 °C, and the cold end temperature was 30 °C (temperature difference 50 °C). After the heat flow reached a steady state (temperature fluctuation ≤ 0.1 °C / 10 min), the hot end temperature T was recorded.hot Cold junction temperature T cold Heat flux density q; each sample was tested 5 times and the average value was taken; total thermal resistance of the sample: R total = (T hot - T cold ) / q; Thermal resistance of bare substrate: R substrate = d substrate / λ substrate (where d) substrate λ is the matrix thickness. substrate (The measured value of the thermal conductivity of the matrix); calculate the total thermal resistance R of the sample. total Thermal resistance R of bare substrate substrate The ratio VR is the average of three sets of parallel samples; the smaller the ratio, the closer it is to 1, indicating a more unobstructed thermal conduction channel between the coating and the substrate; VR = R total / R substrate The results are shown in Table 1.

[0090] Table 1. Thermal resistance comparison test results

[0091] Example 1 1.12 Example 2 1.16 Example 3 1.18 Comparative Example 1 1.72 Comparative Example 2 1.68 Comparative Example 3 1.58 Comparative Example 4 1.42 Comparative Example 5 1.35 Comparative Example 6 1.28 Comparative Example 7 1.52 Comparative Example 8 1.22

[0092] (2) Adhesion test after thermal cycling: Refer to standard GB / T 9286-2021 "Cross-cut test of paints and varnishes" and GB / T 2423.22 standard; thermal cycling: temperature range -40℃~85℃, each cycle is 2 hours (heating for 30 minutes, holding at high temperature for 30 minutes, cooling for 30 minutes, and holding at low temperature for 30 minutes), and samples are taken for testing after 100, 500, and 1000 thermal cycles respectively; 3 parallel samples are prepared for each test item of each group of samples. The samples of Examples 1-3 and Comparative Examples 1-8 are placed in a high and low temperature alternating test chamber and thermal cycling test is carried out under the above conditions. The samples are taken out before thermal cycling, after 100, 500, and 1000 cycles respectively, and placed at room temperature for 24 hours, referring to GB / T 9286-2021, the adhesion of the inner and outer coatings to the substrate was tested using the cross-cut method (blade spacing 2mm, 6×6 cuts). The grading standard was: Grade 0 (best, perfectly smooth cut edges, no cuts peeling off) to Grade 5 (worst). For three parallel samples with the same grade, only one value was taken. If there were different grades, the value was "≤n", where n was the highest grade among the three parallel samples. The results are shown in Table 2. A comparison of the microscopic images of the outer surface of a sample from Example 1 after 1000 thermal cycles with those of samples from Comparative Examples 1-4 is shown below. Figure 3 As shown, the samples in Comparative Examples 1-4 all showed a large number of defects such as cracks on their surfaces, while the samples in the embodiment were still able to maintain structural integrity after 1000 thermal cycles.

[0093] Table 2 Adhesion test results after thermal cycling

[0094] Example 1 Level 0 / Level 0 Level 0 / Level 0 Level 0 / Level 0 Level 0 / ≤ Level 1 Example 2 Level 0 / Level 0 Level 0 / Level 0 Level 0 / Level 0 ≤1 level / ≤1 level Example 3 Level 0 / Level 0 Level 0 / Level 0 Level 0 / Level 0 ≤ Level 1 / Level 1 Comparative Example 1 Level 0 / Level 0 Level 1 / Level 1 Level 2 / Level 3 ≤4 levels / 4 levels Comparative Example 2 Level 0 / Level 0 ≤ Level 1 / Level 1 Level 2 / Level 2 ≤4 levels / ≤4 levels Comparative Example 3 Level 0 / Level 0 Level 1 / Level 1 Level 2 / Level 3 Level 3 / ≤4 Comparative Example 4 Level 0 / Level 0 ≤ Level 1 / Level 1 Level 2 / Level 2 Level 3 / Level 3 Comparative Example 5 Level 0 / Level 0 Level 0 / ≤ Level 1 ≤ Level 1 / 2 Level 1 / Level 3 Comparative Example 6 Level 0 / Level 0 ≤1 level / 0 level Level 1 / ≤ Level 1 Level 2 / Level 1 Comparative Example 7 Level 0 / Level 0 ≤1 level / ≤2 level Level 2 / Level 3 ≤4 levels / 4 levels Comparative Example 8 Level 0 / Level 0 ≤1 level / 0 level Level 1 / Level 0 Level 2 / ≤ Level 1

[0095] (3) Simulated working condition overall temperature rise test: A closed test chamber (cubic chamber) with a volume of 1m³ was constructed, and the shell samples prepared in Example 1 and Comparative Examples 1-8 were installed as the side walls of the chamber; a 500W constant power heating source was placed at the geometric center inside the chamber, and the ambient temperature was controlled at 25℃±2℃; three temperature measuring points were arranged along the height direction (vertical direction) inside the chamber, located at 1 / 4 (lower part), 1 / 2 (middle part, i.e., geometric center height) and 3 / 4 (upper part) of the height inside the chamber, respectively, with each measuring point located at the geometric center of the horizontal cross section of the chamber; the shell samples were arbitrary. K-type thermocouples were placed at the geometric center and four corners of the outer surface of one sidewall, and connected to a multi-channel temperature recorder. After continuous power-on for 2 hours, the temperature of the air inside the cavity when it reached steady state (the average of the three temperature measurement points) and the average temperature of each measurement point on the outer surface of the shell when the air inside the cavity reached steady state were recorded. The criterion for determining that the air inside the cavity reached steady state was that the temperature fluctuation of each monitoring point inside the cavity did not exceed ±0.5℃ within 10 minutes. Each group of samples was tested 3 times, and the average value was taken. The results are shown in Table 3. The lower the steady-state air temperature inside the cavity and the higher the average temperature of the outer surface of the shell, the better the heat dissipation performance of the shell.

[0096] Table 3 Overall Temperature Rise Test Results under Simulated Operating Conditions

[0097] Example 1 52.3℃ 47.5℃ Comparative Example 1 68.7℃ 32.4℃ Comparative Example 2 67.2℃ 33.1℃ Comparative Example 3 62.5℃ 35.6℃ Comparative Example 4 61.8 ℃ 36.2℃ Comparative Example 5 59.7℃ 38.5℃ Comparative Example 6 57.3℃ 40.2℃ Comparative Example 7 62.1℃ 35.9℃ Comparative Example 8 53.8℃ 46.2℃

[0098] (4) The basic properties of the outer coating, inner coating and overall shell of the substrate in Example 1 were tested respectively. The basic properties of the overall shell included the waterproof and dustproof rating test; the basic properties of the outer coating and inner coating of the substrate included corrosion resistance and hardness. The results are shown in Table 4.

[0099] Water and dust resistance rating of the outer casing: Refer to standard GB / T 4208-2017;

[0100] Corrosion resistance testing: Refer to standard GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test"; Salt spray solution: 5% sodium chloride solution (mass fraction); Solution pH value: 6.5~7.2 (neutral); Test temperature: 35±2℃; Salt spray deposition rate: 1.0~2.0 mL / (h·80cm) 2); Sample placement: Placed at an angle of 20±5° to the vertical direction; Test cycle: 720 hours; Start the salt spray chamber and spray continuously until the specified cycle. Remove the sample, gently rinse it with running water not exceeding 35°C for 5 minutes, then rinse it with distilled water and dry it; Then, based on GB / T 6461-2002 (Rating of specimens and test pieces after corrosion tests on metals and other inorganic coatings on metal substrates), rate the corrosion of the sample after the salt spray test. The protection rating (Rp) is used to evaluate the protective ability of the coating on the base metal; Numerical range: 0 (worst) to 10 (best), with a larger number indicating stronger protection.

[0101] Hardness: Refer to standard GB / T 6739-2022 "Determination of Hardness of Paints and Varnishes by Pencil Method";

[0102] Table 4. Results of basic performance tests of the coating

[0103] Example 1: Outer Coating of the Substrate - 9 3H Example 1: Inner Coating of the Substrate - 9 2H Overall shell IP65 - -

[0104] In summary, the thermal resistance contribution of the coating of this application to the substrate is reduced compared with the prior art (Comparative Examples 1 and 2). Based on the overall temperature rise test results under simulated working conditions, the embodiments of this application also have better thermal conductivity and heat dissipation performance compared with the prior art. In addition, the coating of this application has superior heat resistance and corrosion resistance, and can provide basic protection performance.

[0105] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A non-powered, high-efficiency heat dissipation housing for electrical equipment, characterized in that: It includes a substrate, an inner coating, and an outer coating. The inner coating is attached to the inner surface of the substrate, and the outer coating is attached to the outer surface of the substrate. The thickness of the substrate is 4~6mm, the thickness of the inner coating is 60~70μm, and the thickness of the outer coating is 80~100μm. The matrix was prepared from silicon carbide particle-reinforced aluminum matrix composite material; The inner coating comprises the following components in parts by weight: 40-45 parts of cashew nut shell powder-furfurylamine type benzoxazine / acrylate IPN resin precursor, 20-25 parts of phenylboronic acid / dopamine composite modified thiolated boron nitride / vinylened silicon carbide complex, 10-13 parts of aminated alumina, 5-10 parts of cashew nut shell powder glycidyl ether, 30-40 parts of propylene glycol methyl ether acetate, 0.5-0.6 parts of organotin catalyst, and 0.3-0.5 parts of benzoyl peroxide initiator; The outer coating comprises the following components in parts by weight: 45-50 parts of cyclic carbonated polysiloxane, 15-20 parts of glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer, 5-8 parts of polyamine curing agent, 25-28 parts of amine-modified carbon fiber doped ZIF-8 derivative supported graphene derivative / aluminum nitride composite, 0.5-1 parts of DBU / TU bicomponent catalyst, and 30-40 parts of mixed solvent; the mixed solvent is propylene glycol methyl ether acetate and butyl acetate in a volume ratio of 1:

1.

2. The high-efficiency heat dissipation housing for electrical equipment without power supply according to claim 1, characterized in that: The carbon fiber doped ZIF-8 derivative is a product of ZIF-8@PVP composite and lignin-based carbon fiber calcined at 610°C.

3. The high-efficiency heat dissipation housing for electrical equipment without power supply according to claim 1, characterized in that: The cashew phenol-furfurylamine type benzoxazine / acrylate IPN resin precursor is obtained by uniformly mixing cashew phenol-furfurylamine type benzoxazine monomer, acrylate prepolymer and crosslinking agent dimethacrylate in a mass ratio of 4:5:

1.

4. The high-efficiency heat dissipation housing for electrical equipment without power supply according to claim 1, characterized in that: The phenylboronic acid / dopamine composite modified with thiolated boron nitride / vinylened silicon carbide was prepared by the following method: thiolated boron nitride and vinylened silicon carbide were dispersed in N,N-dimethylformamide at a mass ratio of 2:1, and 3% (by mass) of the total mass of thiolated boron nitride and vinylened silicon carbide photoinitiator 2,2-dimethoxy-2-phenylacetophenone was added. The mixture was reacted under ultraviolet light for 2-4 hours. Subsequently, the phenylboronic acid / dopamine composite was added at a mass of 6% (by mass of the total mass of thiolated boron nitride and vinylened silicon carbide), and the mixture was stirred for another 2-4 hours. After centrifugation, washing, and drying, the phenylboronic acid / dopamine composite modified with thiolated boron nitride / vinylened silicon carbide was obtained.

5. The high-efficiency heat dissipation housing for electrical equipment without power supply according to claim 1, characterized in that: The aminated alumina was prepared by dispersing 30 nm α-alumina nanoparticles in toluene, adding 5% γ-aminopropyltriethoxysilane by mass of the α-alumina nanoparticles, and refluxing at 110 °C for 6-8 hours. After the reaction was completed, the alumina was centrifuged, washed, and vacuum dried at 60 °C for 12 hours to obtain aminated alumina.

6. The high-efficiency heat dissipation housing for electrical equipment without power supply according to claim 1, characterized in that: The glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer was prepared by the following method: glycidyl methacrylate, perfluorohexyl ethyl methacrylate and itaconic acid were mixed and dissolved in butyl acetate at a molar ratio of 3:2:1, and 1% of azobisisobutyronitrile initiator (total mass of monomers) was added. The mixture was heated to 70°C under nitrogen protection, stirred and reacted for 12 hours, precipitated in diethyl ether, and dried under vacuum to obtain the terpolymer.

7. The high-efficiency heat dissipation housing for electrical equipment without power supply according to claim 1, characterized in that: The amine-modified carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was prepared by the following method: zinc nitrate hexahydrate and 2-methylimidazole were dissolved in methanol at a mass ratio of 1:2.

5. The 2-methylimidazole solution was slowly added to the zinc nitrate solution under stirring. Then, polyvinylpyrrolidone (PVP) at 20% of the mass of zinc nitrate was added, and the mixture was stirred at room temperature for 2-4 hours. After the reaction was completed, the mixture was centrifuged, washed, and dried at 60°C for 12 hours to obtain the ZIF-8@PVP composite. Lignocellulose-based carbon fibers with a diameter of 100 nm to 200 nm and an aspect ratio of 150, prepared by electrospinning of alkali lignin with a lignin purity of 70%, were dispersed in anhydrous ethanol and ultrasonically treated for 30 minutes to obtain a suspension. ZIF-8@PVP composite was added to the suspension, with a mass ratio of ZIF-8@PVP to lignin-based carbon fibers of 3.5:

1. After stirring and mixing for 2 hours, the mixture was centrifuged and dried at 60 °C to obtain the ZIF-8@PVP / lignin-based carbon fiber composite precursor. The ZIF-8@PVP / lignin-based carbon fiber composite precursor was placed in a tube furnace and heated to 610°C at a heating rate of 3°C / min under argon protection, and held for calcination for 2-4 hours; it was then naturally cooled to room temperature to obtain carbon fiber-doped ZIF-8 derivatives. Graphene oxide, nano-aluminum nitride, and carbon fiber-doped ZIF-8 derivative were dispersed in N,N-dimethylformamide at a mass ratio of 1:2:

10. The mixture was ultrasonically dispersed for 1-2 hours, transferred to a hydrothermal reactor, and reacted at 150°C for 18 hours. After cooling, washing, and drying, a carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was obtained. Carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was dispersed in anhydrous toluene, and 10% (3-aminopropyl)triethoxysilane (by mass) of the carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was added. The mixture was heated to 80℃~110℃ and refluxed for 10h~12h. After centrifugation, washing and drying, amine-modified carbon fiber-doped ZIF-8 derivative-supported graphene derivative / aluminum nitride composite was obtained.

8. The high-efficiency heat dissipation housing for electrical equipment without power supply according to claim 1, characterized in that: The organotin catalyst is dibutyltin dilaurate.

9. The high-efficiency heat dissipation housing for electrical equipment without power supply according to claim 1, characterized in that: The polyamine curing agent is triethylenetetramine; the mass ratio of DBU to TU in the DBU / TU bicomponent catalyst is 2:

1.

10. A method for preparing a non-powered, high-efficiency heat dissipation housing for electrical equipment according to any one of claims 1-9, characterized in that: Includes the following steps: S1. Preparation of the substrate: Silicon carbide particles with a particle size of 10~50μm are placed in an air atmosphere and pre-oxidized at 500℃ for 3 hours to obtain pre-oxidized silicon carbide particles; the pre-oxidized silicon carbide particles are mixed with 6061 aluminum alloy powder at a volume ratio of 45:55, and then magnesium powder accounting for 2% of the total mass of the mixed powder is added. The mixture is ball-milled for 1.5 hours, dried and sieved to obtain a mixed powder; the obtained mixed powder is cold-pressed under a pressure of 50MPa to obtain a cold-pressed blank; the cold-pressed blank is placed in a hot press furnace, and under inert gas protection, the temperature is first raised to 580℃, held at 35MPa for 15 minutes, then raised to 620℃, held at 30MPa for 3 hours, and cooled to room temperature with the furnace to obtain a substrate with a thickness of 4~6mm; the inner and outer surfaces of the substrate are roughened by sandblasting, and then ultrasonically cleaned with acetone and ethanol for 15 minutes in sequence, and dried at 60℃ to obtain a surface-treated substrate for later use; S2. Inner Coating: 40-45 parts of cashew phenol-furfurylamine type benzoxazine / acrylate IPN resin precursor, 20-25 parts of phenylboronic acid / dopamine composite modified mercaptolated boron nitride / vinylened silicon carbide composite, 10-13 parts of aminated alumina, 5-10 parts of cashew phenol glycidyl ether, 30-40 parts of propylene glycol methyl ether acetate, 0.5-0.6 parts of organotin catalyst, and 0.3-0.5 parts of benzoyl peroxide initiator are sequentially added to a dispersion vessel and dispersed at a high speed of 800-1500 rpm for 30-60 minutes. Then, the mixture is transferred to a sand mill and ground to a fineness ≤20 μm to obtain the inner coating. The inner coating is uniformly coated onto the inner surface of the substrate by air spraying. After leveling at room temperature for 10-20 minutes, the coating is placed in an oven for stepwise temperature curing to form an inner coating with a thickness of 60-70 μm. S3, Outer Coating: Mix 45-50 parts of cyclic carbonated polysiloxane, 15-20 parts of glycidyl methacrylate / perfluorohexyl ethyl methacrylate / itaconic acid terpolymer, and 30-40 parts of mixed solvent evenly, then add 25-28 parts of amine-modified carbon fiber doped ZIF-8 derivative supported graphene derivative / aluminum nitride composite, disperse at a high speed of 1000 r / min-2000 r / min for 30 min-60 min, and grind to a fineness ≤20 μm; Before coating, add 5-8 parts of polyamine curing agent and 0.5-1 parts of DBU / TU two-component catalyst, stir evenly, and mature for 10-20 minutes to obtain the outer coating; use air spraying to evenly coat the outer coating onto the outer surface of the substrate; after leveling at room temperature for 15-30 minutes, cure at 100℃ for 4 hours to form an outer coating with a thickness of 80μm-100μm. S4. After coating the inner and outer surfaces of the substrate, allow it to cool naturally to room temperature to obtain a high-efficiency heat dissipation shell material for electrical equipment without power.